THU0372 Effect of tnfi versus nsaid on spinal radiographic progression over 4 years in early ankylosing spondylitis: results from two observational cohorts in south korea. (15th June 2017) - Park, JW; Kim, MJ; Park, JK; Lee, YJ; Lee, EB; Song, YW; Lee, EY
Abstract : Background: It is uncertain whether early suppression of inflammation by tumor necrosis factor inhibitor (TNFi) leads to a decreased radiographic progression in axial spondyloarthritis (axSpA). Objectives: To compare the radiographic progression over 4 years in patients with early ankylosing spondylitis (AS) using TNFi versus nonsteroidal antiinflammatory drug (NSAID) Methods: A total of 215 patients with early AS (symptom duration<10 years) were included based on the availability of radiographs at baseline and 2- and/or 4-years of follow up. Among them, 135 patients with TNFi were from SNUH-biologics cohort (TNFi group) and other 80 patients with NSAID were from control cohort in Seoul National University Bundang Hospital (NSAID group). Radiographic progression was assessed by two blinded readers using modified Stokes AS Spinal Score (mSASSS). Linear mixed model was applied to compare the radiographic progression between the two groups after adjustment for clinical factors. We also performed a sensitivity analysis after the propensity score matching in which age, smoking status, baseline CRP and baseline mSASSS were included as covariates. Results: Patients in the TNFi group showed higher baseline BASDAI (6.7 vs. 3.1) and CRP (2.2 vs. 1.1mg/dL) as compared with those in the NSAID group. There were no differences between the two groups regarding age, gender, HLA-B27, smoking status and baseline radiographic damage. Overall, radiographic progression rate (95% CI) during the observation was 0.72 (0.57–0.87) unit/year. TNFi group showed significantly slower progression than NSAID group (β=-0.33 unit/year, p=0.042). This result was consistent after adjusting for age, smoking status, baseline CRP and presence of baseline syndesmophytes (β=-0.50 unit/year, p=0.001) (Table). In the subgroup analysis of patients without baseline syndesmophytes, TNFi group showed no radiographic progression over time whereas NSAID group did not (0.03 [-0.22–0.27] vs. 0.45 [0.20–0.71] unit/year). These results were not changed when the same analysis was performed in the post-matched population (78 TNFi group vs. 78 NSAID group). Conclusions: In patients with early AS, TNFi led to a decreased radiographic progression as compared with NSAID treatment. This result suggests that early and durable suppression of inflammation using TNFi can have beneficial effect on the radiographic outcome of AS. Disclosure of Interest: None declared